(untitled) (International Journal of Medical and Surgical Sciences, 2022)
The alteration of the senses of taste and smell in relation to COVID-19 is a widely known phenomenon; however, this alteration has not been exhaustively characterized in the international literature. The following study is proposed with the aim of describing the alterations in the senses of taste and smell in relation to COVID-19 by means of their subjective evaluation. The nature of the study is observational, descriptive and cross-sectional, and was applied to patients who sought medical attention via remote consultations carried out on virtual platforms of the Service of Otorhinolaryngology and Head and Neck Surgery of the Clínicas Hospital, San Lorenzo, between the months of March and October of 2021. We included 440 patients aged 31.3 ± 9.9 years (18 to 60 years), 308 (70%) female, 388 (88%) from urban areas, with evidence of infection by SARS-CoV-2 by RT-PCR in 260 (59%), predominantly without comorbidities 232 (53%), with fever as the most frequently reported symptom 352 (80%), treated more frequently with NSAIDs 208 (47%) and/or Paracetamol 216 (49%). Both taste and smell alterations in patients who have had COVID-19 have been shown to appear more frequently 1 to 7 days after the onset of symptoms (207 for smell, 184 for taste), occurring more frequently with a total decrease of both senses (anosmia 302 and ageusia 216), recovering completely in most cases (214 and 216) and within a period of 1 to 4 weeks (140 and 130).